Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen melalui Store Atmosphere di Restoran XYZ - Feby Anugrah Wati; Saepul Jamaludin; Putri Patricia Sihotang; Neng Erni Fitriani; Endang Silaningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
One of the key elements in a company is customer service, which must be supported by a conducive environment. A supportive environment can be an added value for the company. Companies that sell products must consider that good service will create a positive image in the eyes of customers, making them feel that their needs are met. This study examines the service model and mechanism at XYZ Restaurant. The purpose of this article is to identify the model and mechanism used in the budgeting process at XYZ Restaurant. The research method employed is library research. The findings indicate that XYZ Restaurant applies both Top-Down and Bottom-Up budgeting approaches and is capable of adopting a combined budgeting approach. The budgeting process at XYZ Restaurant involves setting the company's vision and strategy, budgeting determination, communication and commitment, budget implementation, as well as monitoring and evaluation.